KONSEP PENDIDKAN ISLAM MASA DEPAN - Sukari; Ilma yulqowim; Muhamad Abdul Azis (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
Islamic education is confronted with major challenges due to the rapid development of digital technology, social change, and increasingly complex global dynamics. This article aims to examine the concept of future Islamic education by emphasizing the reconstruction of Islamic values and learning innovations that are relevant to contemporary demands. This study employs a qualitative approach using a library research method, drawing on primary and secondary sources that discuss the philosophy of Islamic education, educational challenges in the digital era, and models for the development of Islamic education. The findings indicate that future Islamic education must be built upon a strong philosophical and normative foundation derived from the Qur’an and Hadith, while remaining adaptive to technological advancements. The integration of the values of tawhid, adab, and akhlaq with digital-based learning innovations is key to shaping insan kamil who are faithful, knowledgeable, and globally competitive. Thus, Islamic education functions not only as a transmitter of scholarly tradition but also as a civilizational solution in the modern era.